KELIMPAHAN BIVALVIA DI EKOSISTEM LAMUN PANTAI PUDING KABUPATEN BANGKA SELATAN - Mutiara Febrina; Wahyu Adi; Arief Febrianto (Department of Aquatic Resources Management, Faculty of Agriculture, Fisheries, and Biology, University of Bangka Belitung, 2018)
Puding Beach is administratively located in Pasir Putih Village, Tukak Sadai District, South Bangka Regency. As a coastal area, Puding Beach holds natural resource potential in both marine tourism and biota diversity. This study aims to analyze the abundance and distribution of bivalves and the seagrass beach community structure. This research was conducted in March 2018. The research method used was purposive sampling. Whereas for analysis of water quality characteristics and bivalve abundance, use main component analysis (Principle component analysis / PCA). The results showed that there were 6 species of seagrass and 7 species of bivalves at all stations. Each station I, II and III is dominated by the bivalve type Gafrarium tumidium with different seagrass species density. The highest density of seagrass species at stations I, II and III were Halodule uninervis (141 ind / m), Enhalus acoroides (7 ind / m) and Cymodocea serrulata (38 ind / m). Based on the analysis of main components can be seen the description of the condition to research location and can be seen the correlation between the existing bivalve abundance and the condition of the waters in all the research stations described in the F1-F2 factorial field. Important information on the main component axis is centered on the 2 main axes F1 (82.38%) and F2 (4.62%) of the total percentage. Bivalvia distribution analysis at Puding Beach is uniform and clustered based on habitat characteristics and environmental parameters that influence the life of bivalves